CYP74C3 and CYP74A1, plant cytochrome P450 enzymes whose activity is regulated by detergent micelle association, and proposed new rules for the classification of CYP74 enzymes. (25th October 2006) - Hughes, R.K.; Belfield, E.J.; Casey, R.
Abstract : CYP74C3 (cytochrome P450 subfamily 74C3), an HPL (hydroperoxide lyase) from Medicago truncatula (barrel medic), and CYP74A1, an AOS (allene oxide synthase) from Arabidopsis thaliana, are key membrane-associated P450 enzymes in plant oxylipin metabolism. Both recombinant detergent-free enzymes are monomeric proteins with dual specificity and very low enzyme activity that can be massively activated with detergent. This effect is a result of the formation of a complex between the protein monomer and a single detergent micelle and, in the case of CYP74A1, has a major effect on the substrate specificity of the enzyme. Association with a detergent micelle without an effect on protein oligomeric state represents a new mechanism of activation for membrane-associated P450 enzymes. This may represent a second unifying feature of CYP74 enzymes, in addition to their known differences in reaction mechanism, which separates them functionally from more classical P450 enzymes. Highly concentrated and monodispersed samples of detergent-free CYP74C3 and CYP74A1 proteins should be suitable for structural resolution. On the basis of recent evidence for incorrect assignment of CYP74 function, using the current rules for CYP74 classification based on sequence relatedness, we propose an alternative based on substrate and product specificity for debate and discussion.